Evaluation Of Genetic Stock Of Mucuna Pruriens Baker non DC. For Yield ,L-DOPA Content And Nitrogen Fixing Potential In Coconut Garden - Ann Samuel (Department of Horticulture, College of Agriculture, 2000)
The present study titled "Evaluation of genetic stock of Mucuna pruriens Baker non DC. for yield, L-DOPA content and nitrogen fixing potential in coconut garden" was carried out at the Department of Plantation Crops and Spices, College of Agriculture, Vellayani from May 1999 to January 2000. Seeds of twenty five different accessions were collected from inside and outside the state. They were subjected to seed characterization and seed germination studies. Based on the germination rate, ten accessrons with high germination percentage were selected. These were raised under coconut shade. Various biometric observations were taken at four different stages, viz., pre-flowering, flowering, seeding and seed maturation state. These observations included biomass yield, root yield and seed yield. Phytochemical analysis was carried after crop harvest to estimate the quantity of L-DOPA present in the seeds of each accession. Soil tests were carried out to determine the amount of nitrogen fixed in the soil by the accessions.